ANALISIS PROSES COLLABORATIVE GOVERNANCE DALAM PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) DI KABUPATEN PURBALINGGA - Hayyu Gress Violin; Dyah Lituhayu (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
The Corporate Social Responsibility (CSR) program is an important instrument in supporting regional development because it can complement the limitations of the government budget through targeted and sustainable contributions from the private sector. Purbalingga Regency still faces obstacles in implementing the CSR Program, in terms of the lack of a CSR Forum, the lack of collaborative governance between actors, and several companies implementing CSR programs independently. This study aims to analyze the collaborative governance process in the formation of a CSR forum to support the Corporate Social Responsibility (CSR) program in Purbalingga Regency and its inhibiting factors. The analysis uses the Collaborative Governance process theory according to Ansell & Gash (2008), which goes through five stages: face-to-face dialogue, building trust, commitment to the process, mutual understanding, and interim results. Another theory used is the factors influencing collaboration according to Mattesich & Monsey (1992), which goes through six stages: environment, membership, process/structure, communication, goals, and resources. The research approach used is descriptive qualitative through in-depth interviews and documentation of local government, DPRD, and the private sector. The results of the study show that the implementation of the CSR Program in Purbalingga Regency has not been optimal, as indicated by the local government's lack of facilitative and coordinative role in implementing Regional Regulation No. 10 of 2023, the absence of a CSR Forum as a collaborative institutional platform, and weak communication between the executive and legislative branches, accompanied by a lack of dialogue between actors. In addition, differences in interests between the local government and the private sector that have not been managed through collaborative mechanisms also hinder the formation of trust, shared commitment, and the integration of CSR into regional development governance in a systematic and sustainable manner.